F- transport law in a coal mine goaf filled with gangue and its variations characteristics with Darcy flow velocity - ZHAO Li; JIA Xiangteng; ZHANG Qing; XU Feng; ZHU Kaipeng; KONG Weifang; XING Mingfei; JIN Yi (河南理工大学学报. 自然科学版)
During coal mining， the massive accumulation of coal gangue and its pollution effects on groundwater have become pressing issues in ecological environment management and resource utilization.ObjectivesUsing coal gangue to backfill goafs as a storage space for purified mine water can not only achieve resource utilization of coal gangue but also help remove fluoride from mine water. This provides an economical and environmentally friendly solution.MethodsThis study focuses on fluoride in mine water， using coal gangue from the Baode mine goaf as the backfill medium. Based on the hydrogeological conditions of the study area， column simulation experiments were performed at 25 °C with Darcy flow velocities of 6.24， 3.12， and 1.56 cm/h. Experimental data were numerically simulated using the Convection-Dispersion Equation （CDE） model and the Two-Site Model to explore the transport behavior of fluoride under different flow velocities.ResultsThe experimental results showed that chloride acted as a non-reactive tracer， and their breakthrough time was negatively correlated with flow velocity. The CDE model effectively described their migration behavior， and dispersion increased with the rise in Darcy flow velocity. For F- migration， the Two-Site Model provided a better representation of the migration process compared to the CDE model. Coal gangue demonstrated significant adsorption-retardation effects on fluoride， with the retardation factor R and adsorption capacity increasing as the flow velocity decreased. The equilibrium adsorption site fraction （f value） and distribution coefficient （β value） of fluoride on coal gangue also increased with decreasing flow velocity， while the first-order kinetic adsorption rate constant （α） decreased. This indicates that equilibrium adsorption becomes more dominant as the flow velocity decreases during solute migration. Additionally， as leachate was continuously injected， OH- on the surface of the coal gangue were gradually replaced by F- through ion exchange adsorption， leading to an increase in the pH of the effluent. This pH increase was more pronounced at lower flow velocities.ConclusionsThe results could not only provide a theoretical basis for the purification of high-fluoride mine water but also alleviate the environmental pressure caused by coal gangue accumulation， offering significant environmental and economic benefits with promising potential for broader application.